1998
DOI: 10.1111/1467-6494.00025
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Control Over Age‐Related Changes in Physical Appearance

Abstract: Beliefs about appearance-related changes due to aging were used to test the effects of perceived control and secondary control (acceptance) in a sample of 412 young, early-middle-age, and late-middle-age college-educated adults. Mean difference in aging-related appearance control and hypotheses regarding the adaptiveness of primary and secondary control were examined. Primary control over aging-related appearance was lower in older adults and secondary control was higher. In addition, the results indicated sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 29 publications
5
72
2
3
Order By: Relevance
“…Indeed, the body naturally undergoes a number of changes as women age (e.g., increased hip-to-waist ratio, decrease inskinelasticity).Inthatcontext,high(orunchanged)levelsofbody appreciation could beconsidered indicative of effective coping with these changes. This is consistent with other studies on body image and aging, indicating that acceptance, a hallmark of body appreciation, is among the most used mechanisms for coping with agerelated changes to the body (e.g., Thompson et al, 1998;Tiggemann, 2004;Webster & Tiggemann, 2003). Therefore, we suggest that although young and older women may experience comparable levels of body appreciation, its contribution to women's psychological well-being may vary with age.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the body naturally undergoes a number of changes as women age (e.g., increased hip-to-waist ratio, decrease inskinelasticity).Inthatcontext,high(orunchanged)levelsofbody appreciation could beconsidered indicative of effective coping with these changes. This is consistent with other studies on body image and aging, indicating that acceptance, a hallmark of body appreciation, is among the most used mechanisms for coping with agerelated changes to the body (e.g., Thompson et al, 1998;Tiggemann, 2004;Webster & Tiggemann, 2003). Therefore, we suggest that although young and older women may experience comparable levels of body appreciation, its contribution to women's psychological well-being may vary with age.…”
Section: Discussionsupporting
confidence: 91%
“…44,45 Previous literature 19,20 has suggested that importance of appearance many diminish with age, but in the current study of women aged 35-65 years, there was no relationship between age and appearance importance. Regardless of age, higher importance placed on appearance was related to higher levels of body dissatisfaction and disordered eating.…”
Section: Discussioncontrasting
confidence: 60%
“…A measure drawing on other attributes, such as movement, ability to engage in life, physical pleasure, and body-related accomplishments, as has been suggested in qualitative studies, 22,23 may yield different results. Alternatively, the interpretation of the body function items may account for Consistent with studies by Webster and Tiggemann, 9 and Thompson et al, 20 cognitive reappraisal, that is, altering expectations, or accepting changes to physical appearance that occur with age, was associated with lower levels of body image and eating concerns. Women who engage in cognitive reappraisal may do so because they do not place a great deal of importance on their appearance.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations